KELAYAKAN MAJALAH MATERI KEANEKARAGAMAN HAYATI DARI BUAH BALADOK JEMPARI DAN TITIDAN - Beatha, Y Aprima; Daningsih, Entin; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to determine the feasibility of class X biodiversity material magazines from morphology, nutrient content and fruit fiber of baladok (Burasaia congesta Decne), jempari (Ixora lobbii Loudon) and titidan (Nephelium cuspidatum Blume) that was carried out in Tembawang forest, Bengkayang District. This research was descriptive method using purposive sampling technique. There were two stages of validation, namely instrument validation and media validation. Magazine media was validated by five validators consisting of two lecturers ofÂ biology education FKIP Tanjungpura university, one biology teacher in Pontianak City and two biology teachers in Bengkayang District. Assessment of instrument validation and magazine validation consisted of three aspects and 10 criteria which were calculated using the analysis method of Lawshe Content Validity Ratio (CVR) and Content Validity Index (CVI). Based on the results of the study, instrument validation was said to be feasible to use and corrected, while magazine validation obtained CVR and CVI of 0.99 values on aspects of language, content and construction in accordance with Lawshe's minimum CVR value for five validators so that the magazine was said to be valid and feasible to used as a learning media on material biodiversity in class X high school.Keywords: magazine, biodiversity, baladok, jempari, titidan